(untitled) (BIBECHANA, 2010)
Different types of food additives have been discussed. I have discussed the role of food additives to preserve nutritional values and to maintain desired consistency of the product. The antioxidants and antimicrobials food preservatives have also been studied. Keywords: food additives; preservatives; colorants; sweeteners DOI: 10.3126/bibechana.v6i0.3935 BIBECHANA Vol. 6, March 2010 pp.22-26